Penyimpangan Nilai-Nilai Islam Dalam Bermedia Sosial Siswa Sekolah Menengah Pertama (Studi Siswa SMPN 1 Kota Mojokerto) - Bahrul Ulum, Ahmad; Rozi, Syaikhu (PT. Kreasi Karya Majakata, 2023)
This research aims to analyze the social behavior of students from SMPN 1 Kota Mojokerto in the context of deviations from Islamic values. This study identifies various forms of deviation from Islamic values in the students' social media behavior, such as the misuse of social media to communicate with the opposite gender without considering religious boundaries, the spread of negative or unhelpful content, dissemination of hoaxes, and showcasing extravagance or glamorous lifestyles. These deviations from Islamic values have significant impacts on the formation of students' character and morality. Addressing these deviations from Islamic values can be achieved through collaborative efforts involving the school, teachers, parents, and the community. Enhancing understanding of religious teachings, ethics, and moral values is essential for students through a holistic educational approach. Close cooperation among the school, parents, and the community is necessary to provide intensive monitoring and guidance regarding students' social media behavior. Additionally, raising public awareness about the dangers and negative consequences of deviations from Islamic values in social media behavior is also crucial, and this can be accomplished through campaigns, seminars, or discussions.